Novel Organosulfur Building Blocks for Heterocycle Synthesis - Peruncheralathan, Saravanan; Ila, Hiriyakkanavar (Synlett, 2024)
The present article provides a personalized account of our recent work on the synthesis of substituted and fused five-membered heterocycles using various organosulfur building blocks, derived primarily through base-mediated condensation of active methylene compounds with (het)aryl/alkyl dithioesters, which have not been previously explored. We initially describe the ring-opening transformations of 4-[(methylthio)-(het)aryl-methylene]-2-phenyl-5-oxazolones, leading to the synthesis of functionalized oxazoles, thiazoles, and bisoxazoles. We then go on to focus on the synthesis of substituted benzothiophenes, indoles, and benzofurans, as well as their hetero-fused analogs. These compounds are synthesized via transition-metal-catalyzed intramolecular C–heteroatom (C–S, C–N, C–O) bond formation (via cross-coupling or C–H bond functionalization) of various reactive organosulfur intermediates, derived from base-mediated condensation of 2-bromo(het)arylacetonitriles, acetates, or desoxybenzoins or the corresponding 2-unsubstituted precursors. Finally, we highlight the synthetic applications of a new class of previously unexplored organosulfur building blocks, namely, unsymmetrically substituted 1,3-bis(het)aryl-1,3-monothioketones, derived via base-mediated condensation of ketones with (het)aryl/alkyl dithioesters, for the regioselective synthesis of substituted pyrazoles, isoxazoles, thiophenes, imidazoles, and benzothiophenes.1 Introduction2 4-[(Methylthio)-het(aryl)-methylene]-2-phenyl/2-(2-thienyl)-5-oxazolones: Versatile Templates for the Synthesis of Oxazoles, Thiazoles, and Bisoxazoles3 Synthesis of Benzothiophenes, Indoles, and Benzofurans via Transition-Metal-Catalyzed Intramolecular C–Heteroatom Bond Formation4 1,3-Bis(het)arylmonothio-1,3-diketones and 1,3-Bis(Het)aryl-3-(methylthio)-2-propenones: Versatile Intermediates for the Regioselective Synthesis of Five-Membered Heterocycles5 Conclusion
Keywords: organosulfur building blocks; (het)aryl/alkyl dithioesters; 4-[(methylthio)-het(aryl)-methylene]-2-phenyl-5-oxazolones; transition metal catalyzed intramolecular C-heteroatom bond formation; 1,3-bis(het)aryl-1,3-monothioketones